19
$\begingroup$

Can anyone suggest a method for solving the integral below? I've tried numerous things but have had no luck yet. To be honest I'm not sure an analytical solution actually exists.

$$I=\int\cosh(2x)\sqrt{[\sinh(x)]^{-2/3}+[\cosh(x)]^{-2/3}}\,\textrm{d}x.$$

Thanks.

Here is another attempt I have made:

Let $y=[\tanh(x)]^{2/3}$, and rewrite $I$ such that

$$I=\int\cosh(2x)[\sinh(x)]^{-1/3}\sqrt{1+[\tanh(x)]^{2/3}}\,\textrm{d}x.$$

Then $\textrm{d}x=(3/2)[\tanh(x)]^{1/3}[\cosh(x)]^{2}\,\textrm{d}y$. Therefore

\begin{align*} I&=\frac{3}{2}\int\cosh(2x)[\sinh(x)]^{-1/3}[\tanh(x)]^{1/3}[\cosh(x)]^{2}\sqrt{1+y}\,\textrm{d}y \\ &=\frac{3}{2}\int\cosh(2x)[\cosh(x)]^{5/3}\sqrt{1+y}\,\textrm{d}y \\ &=\frac{3}{2}\int[\cosh(x)]^{11/3}\sqrt{1+y}\,\textrm{d}y +\frac{3}{2}\int[\sinh(x)]^{2}[\cosh(x)]^{5/3}\sqrt{1+y}\,\textrm{d}y \\ &=\frac{3}{2}\int[\textrm{sech}(x)]^{-11/3}\sqrt{1+y}\,\textrm{d}y +\frac{3}{2}\int[\tanh(x)]^{2}[\textrm{sech}(x)]^{-11/3}\sqrt{1+y}\,\textrm{d}y \\ &=\frac{3}{2}\int[\textrm{sech}(x)]^{-11/3}\sqrt{1+y}\,\textrm{d}y +\frac{3}{2}\int[\textrm{sech}(x)]^{-11/3}y^3\sqrt{1+y}\,\textrm{d}y \\ &=\frac{3}{2}\int\frac{(1+y)^{1/2}}{(1-y^3)^{11/6}}\,\textrm{d}y +\frac{3}{2}\int y^{3}\frac{(1+y)^{1/2}}{(1-y^3)^{11/6}}\,\textrm{d}y \\ &=\frac{3}{2}\int\frac{(1+y^3)(1+y)^{1/2}}{(1-y^3)^{11/6}}\,\textrm{d}y \\ &=\frac{3}{2}\int\frac{(1-y^6)(1+y)^{1/2}}{(1-y^3)^{17/6}}\,\textrm{d}y \end{align*}

$\endgroup$
  • $\begingroup$ It would be really great if you showed us what you've done even if it hasn't worked :) $\endgroup$ – clathratus Apr 2 at 18:59
  • $\begingroup$ Have edited my original post. $\endgroup$ – Juggler Apr 3 at 9:20
  • $\begingroup$ Thank you! You have earned an upvote from me :) $\endgroup$ – clathratus Apr 3 at 15:17
  • 1
    $\begingroup$ Nice work for sure and $\to +1$ $\endgroup$ – Claude Leibovici Apr 4 at 8:57
  • 1
    $\begingroup$ I wouldn't be optimistic: WolframAlpha seems to fail. $\endgroup$ – Yves Daoust Apr 4 at 9:01
8
+25
$\begingroup$

$\color{brown}{\textbf{Version of 03.05.19}}$

Are known the identities

$$\begin{cases} \cosh^2t-\sinh^2t = 1\\ 2\cosh^2t = \cosh2t + 1\\ 2\sinh^2t = \cosh2t -1\\ 2\sinh t\cosh t = \sinh 2t\\ \cosh^{-2}t = 1-\tanh^2x\\ \sinh^{-2}t = \coth^2x-1\\ (\tanh x)' = \cosh^{-2}t\\ (\coth x)' = -\sinh^{-2}t. \end{cases}\tag1$$

One can get

$$\cosh^{\large^-\frac23}x + \sinh^{\large-^\frac23}x = \sqrt[{\large3}]{1-\tanh^2x} + \sqrt[{\large3}]{\coth^2x-1},$$ $$\cosh^{\large^-\frac23}x + \sinh^{\large-^\frac23}x = \sqrt[{\large3}]{\coth x - \tanh x} (\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}),\tag2$$ $$\cosh2x = \dfrac{\cosh^2x+\sinh^2x}{\cosh^2x-\sinh^2x} =\dfrac{\coth x + \tanh x}{\cot x - \tanh x}.\tag3$$ Therefore, $$I = \int\cosh2x\sqrt{\cosh^{\large^-\frac23}x + \sinh^{\large^-\frac23}x\,}\,dx,$$ $$I = \int\dfrac{\coth x + \tanh x}{(\coth x - \tanh x)^{\large^\frac56}} \sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}\,dx.\tag4$$

Taking in account that $$\left(\frac65(\sinh x \cosh x)^{\large^-\frac56}\right)' = \dfrac{\coth x + \tanh x}{(\coth x - \tanh x)^{\large\frac56}}$$ (see also Wolfram Alpha), $$\left(\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}\right)' = \dfrac{\left(\coth^{\large^-\frac23}x (1-\coth^2x) + \tanh^{\large^-\frac23}x (1-\tanh^2x)\right)}{6\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}}$$ $$= -\dfrac{(\coth x - \tanh x) \left(\sqrt[{\large3}]{\coth x} - \sqrt[{\large3}]{\tanh x}\right)}{6\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}},$$

is possible the integration by parts: $$I(x) = -\dfrac65 \int\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}\,\mathrm d\left((\sinh x \cosh x)^{\large^-\frac56}\right),$$ $$I(x) = \dfrac35 I_1(x) - \dfrac65\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}\,(\sinh x \cosh x)^{\large^-\frac56},\tag5$$ where $$I_1(x) = \int \left((\sinh x \cosh x)^{\large^-\frac56}\right) \dfrac{\mathrm d\left(\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}\right)}{\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}}. \tag6$$ Let $$\left(\sqrt[{\large3}]{\coth x} - \sqrt[{\large3}]{\tanh x}\right)^2 = y,\tag7$$ then $$\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x} = \sqrt{y+4}\,$$ $$(\sinh x \cosh x)^{-1} = \dfrac{\cosh^2x - \sinh^2x}{\sinh x \cosh x} = \coth x - \tanh x = \sqrt y (y+3),$$ $$I(x) = \dfrac3{10} J\left(\left(\sqrt[{\large3}]{\coth x} - \sqrt[{\large3}]{\tanh x}\right)^2\right) - \dfrac65\sqrt{\sqrt[{\large3}]{\coth x} + \sqrt[{\large3}]{\tanh x}}\,(\sinh x \cosh x)^{\large^-\frac56},\tag8$$ where $$J(y) = \int (y+3)^{\large^\frac56}(y+4)^{\large^-\frac34}\,y^{\large^\frac5{12}}\,dy\tag9,$$

wherein the last integral can be expressed in the closed form of $$\begin{align} &J(y) = \frac2{51} y^{\large^\frac5{12}} \left(-17\cdot 3^{\large^\frac56} F_1\left(\frac5{12}; \frac34, \frac16; \frac{17}{12};-y, -\frac y3\right)\right.\\ & + \left. 5\cdot 3^{\large^\frac56} y F_1\left(\frac{17}{12}; \frac34, \frac16;\frac{29}{12}; -y, -\frac y3\right) + 17 (y+1)^{\large^\frac14} (y+3)^{\large^\frac56}\right) + \mathrm{constant} \end{align}\tag{10}$$ via the Appell hypergeometric function of two variables.

Formulas $(8),(10)$ $\color{brown}{\textbf{present the given integral in the closed form}}.$

$\endgroup$
  • 1
    $\begingroup$ The first identity you state doesn't seem to be correct. If I set $u^3-v^3=1$ then $4(\frac{u-v}{2})^3+3\frac{u-v}{2}=\frac{1}{2}+\frac{3}{2}(u-v)(1-uv)$ which I cannot seem to reduce further unless $uv=1$. Can you provide a proof of the statement? $\endgroup$ – DinosaurEgg Apr 30 at 21:40
  • 1
    $\begingroup$ Alpha not finding a solution is a good indication that no closed-form exists. $\endgroup$ – Yves Daoust May 2 at 7:34
  • 1
    $\begingroup$ In the steps below (3) and above (4) there should be a $$\sqrt[3]{\sinh(2x)}=\sqrt[6]{y^2-1}$$ in the denominator. $\endgroup$ – Diger May 2 at 7:54
  • 1
    $\begingroup$ I agree with the above comment. In fact, according to my working, using the substitution proposed I obtain $$I=\frac{1}{2}\int\left(\frac{\sqrt[3]{\frac{y+1}{2}}+\sqrt[3]{\frac{y-1}{2}}}{\sqrt[3]{\frac{y^2-1}{2}}}\right)^{1/2}\frac{y}{\sqrt{y^{2}-1}}\,\textrm{d}y.$$ Nothing more manageable! $\endgroup$ – Juggler May 2 at 11:17
  • 1
    $\begingroup$ @YuriNegometyanov: definitely hard, and definitely interesting ! $\endgroup$ – G Cab May 4 at 13:54
3
$\begingroup$

Partial answer:

Integration by parts with $$\sf{f(y)=\frac{1-y^6}{(1-y^3)^{17/6}}\implies f'(y)=\frac{y^2(17+5y^3)}{2(1-y^3)^{17/6}}}\\ g'(y)=(1+y)^{1/2}\implies g(y)=\frac23(1+y)^{3/2}$$ gives $$\sf{J=\frac{3}{2}\int\frac{(1-y^6)(1+y)^{1/2}}{(1-y^3)^{17/6}}\,dy=\frac{(1-y^6)(1+y)^{3/2}}{(1-y^3)^{17/6}}-\overbrace{\frac12\int\frac{y^2(1+y)^{3/2}}{(1-y^3)^{17/6}}(17+5y^3)\,dy}^K}$$ and the substitution $\sf{w=1-y^3}$ yields $$\small\sf{K=-\frac16\int\frac{(1+\sqrt[3]{1-w})^{3/2}}{w^{17/6}}(22-5w)\,dw=\overbrace{\frac56\int\frac{(1+\sqrt[3]{1-w})^{3/2}}{w^{11/6}}\,dw}^P-\overbrace{\frac{11}3\int\frac{(1+\sqrt[3]{1-w})^{3/2}}{w^{17/6}}\,dw}^Q}.$$ It is possible to simplify further; let us consider $\sf Q$ first. Integration by parts again with \begin{align}\sf{f(w)=(1+(1-w)^{1/3})^{3/2}}&\sf{\implies f'(w)=-\frac{(1+(1-w)^{1/3})^{1/2}}{2(1-w)^{2/3}}}\\\sf{g'(w)=\frac1{w^{17/6}}}&\sf{\implies g(w)=-\frac6{11w^{11/6}}}\end{align} gives $$\sf{Q=\frac{11}3\left[-\frac{6(1+\sqrt[3]{1-w})^{3/2}}{11w^{11/6}}-\frac3{11}\int\frac{(1+(1-w)^{1/3})^{1/2}}{w^{11/6}(1-w)^{2/3}}\,dw\right]}$$ and the substitution $\sf{t=1+(1-w)^{1/3}}$ yields $$\sf{Q=-\frac{2(1+\sqrt[3]{1-w})^{3/2}}{w^{11/6}}+3\int\frac{\sqrt t}{(1-(t-1)^3)^{11/6}}\,dt}$$ and since $\sf{1-(t-1)^3=(2-t)(t^2-t+1)}$, the substitution $\sf{s=2-t}$ results in $$\sf{\int\frac{\sqrt t}{(1-(t-1)^3)^{11/6}}\,dt=\int\frac{\sqrt{2-s}}{s^{11/6}(s^2-3s+3)^{11/6}}\,ds.}$$ Using a similar procedure, we find that $$\sf{P=-\frac{(1+\sqrt[3]{1-w})^{3/2}}{w^{5/6}}+\frac32\int\frac{\sqrt{2-s}}{s^{5/6}(s^2-3s+3)^{5/6}}\,ds}$$ and putting back $\sf{w=1-y^3}$, we can now derive a simpler expression for $\sf J$: $$\sf{J=\frac{(1-y^6)[(1+y)^{3/2}-y^{3/2}]}{(1-y^3)^{17/6}}+3\int\frac{\sqrt{2-s}}{s^{11/6}(s^2-3s+3)^{11/6}}\,ds-\frac32\int\frac{\sqrt{2-s}}{s^{5/6}(s^2-3s+3)^{5/6}}\,ds}.$$

$\endgroup$
  • 2
    $\begingroup$ That font looks sweet, by the way! :P $\endgroup$ – Mr Pie Apr 28 at 8:30
0
$\begingroup$

Other attempt:

With $t=e^{2x}$, and omitting a constant factor, you obtain the rational form

$$\int (t+t^{-1})\sqrt{(t^{1/2}-t^{-1/2})^{-2/3}+(t^{1/2}+t^{-1/2})^{-2/3}}\frac{dt}t$$

or

$$\int (t^2+1)(t^2-1)^{-1/3}\sqrt{(t-1)^{2/3}+(t+1)^{2/3}}\,t^{-4/3}\,dt.$$

Nothing more appetizing.

$\endgroup$
0
$\begingroup$

Thanks to Yuri for his working. Very helpful. I believe I have arrived at the solution now

\begin{align*} I&=\int\cosh(2x)\sqrt{[\sinh(x)]^{-2/3}+[\cosh(x)]^{-2/3}}\,\textrm{d}x \\ &=\int\cosh(2x)\biggl[\frac{\sinh(2x)}{2}\biggr]^{-1/6}[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}\,\textrm{d}x \\ &=\frac{6}{5}\int\frac{\textrm{d}}{\textrm{d}x}\biggl[\frac{\sinh(2x)}{2}\biggr]^{5/6} [\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}\,\textrm{d}x \\ &=\frac{6}{5}\biggl[\frac{\sinh(2x)}{2}\biggr]^{5/6}[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2} \\&\quad-\frac{6}{5} \int\biggl[\frac{\sinh(2x)}{2}\biggr]^{5/6}\frac{\textrm{d}}{\textrm{d}x}[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}\,\textrm{d}x. \end{align*}

Now

\begin{equation*} \frac{\textrm{d}}{\textrm{d}x}[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2} =\frac{1}{6}\biggl[\frac{\sinh(2x)}{2}\biggr]^{-1}\frac{[\sqrt[3]{\tanh(x)}-\sqrt[3]{\coth(x)}]}{[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}}. \end{equation*}

Therefore

\begin{align*} I_{2}&=\frac{6}{5} \int\biggl[\frac{\sinh(2x)}{2}\biggr]^{5/6}\frac{\textrm{d}}{\textrm{d}x}[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}\,\textrm{d}x \\&= \frac{1}{5}\int\biggl[\frac{\sinh(2x)}{2}\biggr]^{-1/6} \frac{[\sqrt[3]{\tanh(x)}-\sqrt[3]{\coth(x)}]}{[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}}\,\textrm{d}x. \end{align*}

Let $y=[\sqrt[3]{\tanh(x)}+\sqrt[3]{\coth(x)}]^{1/2}$ then

\begin{equation*} I_{2}= \frac{6}{5}\int\biggl[\frac{\sinh(2x)}{2}\biggr]^{5/6}\,\textrm{d}y=\frac{6}{5}\int[\coth(x)-\tanh(x)]^{-5/6}\,\textrm{d}y . \end{equation*}

After a bit of work it is possible to show that

\begin{equation*} \coth(x)-\tanh(x)=(y^{4}-1)\sqrt{y^{4}-4}. \end{equation*}

Therefore

$$I=\frac{6}{5}\biggl\{\biggl[\frac{\sinh(2x)}{2}\biggr]^{5/6}y-\int(y^{4}-1)^{-5/6}(y^{4}-4)^{-5/12}\,\textrm{d}y\biggr\},$$

where $y$ is as above and the integral can be written in terms of the hypergeometric function.

A very interesting problem! Thanks to all.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.